Influenza response planning for the centers of excellence for influenza research and surveillance: Science preparedness for enhancing global health security. Issue 4 (19th April 2020) - Moore, Kristine A.; Ostrowsky, Julia T.; Mehr, Angela J.; Osterholm, Michael T.; ,
Abstract: Background: The Centers of Excellence for Influenza Research and Surveillance (CEIRS) network, funded by the US National Institutes of Health, has been operational since 2007 and is tasked with conducting research to improve understanding of influenza viruses. Recently, CEIRS developed an Influenza Response Plan (IRP) to improve science preparedness for the network. Methods: Development of the IRP involved a collaborative process between project staff, CEIRS center directors or their designees, and NIAID CEIRS leadership (referred to as the Pandemic Planning Advisory Committee [PPAC]). Project staff identified and summarized the response capabilities of each center and then worked with the PPAC to identify and rank research priorities for an emergency response using a modified Delphi method. Results: Key elements of the response plan include tables of response capabilities for each CEIRS center, a framework that outlines and ranks research priorities for CEIRS during an emergency situation, and an operational strategy for executing the research priorities. Conclusions: The CEIRS IRP highlights the importance of enhancing science preparedness in advance of an influenza pandemic or other influenza‐related zoonotic incident to ensure that research can be carried out expeditiously and effectively in emergency situations and to improve global health security.